Learning media: Video podcast for biodiversity exploration - Rejeki, Nur Intan Tri; Jamilah, Jamilah; Arif , Wiwin Pramita; Syamsul, Syamsul; Maulana, Andi; Maulidya, Fakhirah (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2024)
Biodiversity includes the distribution of flora and fauna, rainforests, diversity of benefits, and conservation. However, no media, especially video recordings used in the educational process, are available for public viewing and listening. Therefore, it is important to provide valuable and impactful educational resources in the form of video podcasts to facilitate their learning and understanding of biodiversity topics. This study aimed to develop a video podcast learning media on biodiversity material for class X MA DDI Maspul in Bone Regency, assess its validity, evaluate its practicality, and determine its effectiveness. The research method used is R&D (research and development), which refers to the ADDIE model. The subjects of this study were 24 students of class X MA DDI Maspul. The research instruments included validation sheets, student and educator response questionnaires, and learning outcome test questions. Data collection techniques through questionnaires and tests. Quantitative data including validation results, practical scores, and learning outcomes were analyzed descriptively. The results showed, that the developed video podcast learning material demonstrated high validity (average score of 3.7) and was considered very practical by educators and students (average score of 3.2). Additionally, it proved highly effective, with students achieving an average score of 87.6, indicating 100% effectiveness in the learning process. In conclusion, the video podcast learning media developed in this study is valid, practical, and highly effective, making it a suitable teaching tool.